Relationship between serum vitamin D levels and the atherogenic index of plasma: a study based on NHANES database 2011–2018 - Hu, Tingting; Zhang, Ying; Chen, Zhu; Su, Jun (Frontiers in Nutrition, 2024)
Objective This study aims to investigate the relationship between serum vitamin D levels and the atherogenic index of plasma (AIP) in individuals aged 20 years and above, as well as analyze potential influencing factors. Methods A total of 9,637 participants aged 20 years and above from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2018 were included in this study. The AIP was calculated using the formula log[triglycerides (TG)/high-density lipoprotein cholesterol (HDL-C)]. Due to the skewed distribution of serum vitamin D levels in the study population, a normal transformation was performed. Weighted multivariate linear regression models were used to assess the linear relationship between the transformed serum vitamin D levels and AIP. Subgroup analysis was conducted by stratifying the data based on age, gender, and race to evaluate the stability of the relationship between serum vitamin D levels and AIP in different populations. In addition, a smooth curve fitting and generalized linear models were employed to examine the nonlinear relationship between serum vitamin D levels and AIP. Results After controlling for confounding factors, the multivariate linear regression analysis revealed a negative correlation between serum vitamin D levels and AIP [β = −0.0065, 95% CI: (−0.0106, −0.0024)]. This negative correlation was significant in male participants [β = −0.0077, 95% CI: (−0.0142, −0.0011)], Non-Hispanic Black participants [β = −0.0135, 95% CI: (−0.0211, −0.0059)], as well as participants aged 40–50 [β = −0.0124, 95% CI: (−0.0226, −0.0022)] and 60–70 [β = −0.0118, 95% CI: (−0.0214, −0.0023)]. Furthermore, a nonlinear relationship and saturation effect were observed between the transformed serum vitamin D levels and AIP, with a turning point at 8.5617 nmol/L. Conclusion Our study revealed a significant negative correlation and saturation effect between serum vitamin D levels and AIP.